Do Growth Rates Depend on the Initial Firm Size? Evidence for the German Agribusiness - Julia Hoḧler; Rainer Kuḧl (German Journal of Agricultural Economics (GJAE), 2016)
The agribusiness is in flux: how will the population of firms develop, and which consequences will arise for competition? In 1931, GIBRAT stated the firm size and growth rate to be independent. Testing the validity of Gibrat's Law for the agribusiness allows drawing conclusions on future developments of concentration. After the examination of 454 manufacturing downstream enterprises in Germany, we reject Gibrat's Law and find small firms to grow stronger than bigger firms in relation to their initial size. Our results emphasize the application of Gibrat's Law to subsectors and size classes as well as to the agribusiness as a whole.
Keywords: 330